Community Member and Faith Leader Perspectives on the Process of Building Trusting Relationships between Communities and Researchers. Issue 1 (9th January 2014) - Lakes, Kimberley D.; Vaughan, Elaine; Pham, Jennifer; Tran, Tuyet; Jones, Marissa; Baker, Dean; Swanson, James M.; Olshansky, Ellen
Abstract In the first phase of this research, we conducted, audio‐recorded, and transcribed seven focus groups with more than 50 English‐ or Spanish‐speaking women of childbearing age. Qualitative analysis revealed the following themes: (1) expectation that participation would involve relationships based on trust that is built over time and impacted by cultural factors; (2) perceived characteristics of research staff that would help facilitate the development of trusting relationships; (3) perceptions about the location of the visits that may affect trust; (4) perceptions of a research study and trust for the institution conducting the study may affect trust; (5) connecting the study to larger communities, including faith communities, could affect trust and willingness to participate. In the second phase of this research, we conducted, recorded, transcribed, and analyzed interviews with leaders from diverse faith communities to explore the potential for research partnerships between researchers and faith communities. In addition to confirming themes identified in focus groups, faith leaders described an openness to research partnerships between the university and faith communities and considerations for the formation of these partnerships. Faith leaders noted the importance of finding common ground with researchers, establishing and maintaining trusting relationships, and committing to open, bidirectional communication.